Quality Assurance of Education in Senior High School during Covid-19 Pandemic - Hasan Baharun; Akmal Mundiri; Zamroni Zamroni; Faizzatul Jannah (AL-ISHLAH: Jurnal Pendidikan, 2021)
During the Covid-19 pandemic, SMA Nurul Jadid, Probolinggo, East Java created a quality assurance system to survive and win the rivalry between educational institutions. This study aims to understand the meaning behind quality assurance activities at SMA Nurul Jadid, Probolinggo using a qualitative case study approach. Researchers conducted interviews with committees, principals, vice-principals, teachers, and observations and documentation were carried out in this research. Data gathering, data reduction, display, and conclusion are steps in the data analysis process. The findings revealed that SMA Nurul Jadid's quality assurance system was implemented and evaluated through systematic planning, including numerous school members and the community, quality assurance implementation, and evaluation. This study has implications for the significance of educational institutions maintaining excellence to sustain the public trust built up over the years.